#MeToo and the Politics of Social Change - Fileborn, Bianca; Loney-Howes, Rachel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
#MeToo has sparked a global re-emergence of sexual violence activism and politics. This edited collection uses the #MeToo movement as a starting point for interrogating contemporary debates in anti-sexual violence activism and justice-seeking. It draws together 19 accessible chapters from academics, practitioners, and sexual violence activists across the globe to provide diverse, critical, and nuanced perspectives on the broader implications of the movement. It taps into wider conversations about the nature, history, and complexities of anti-rape and anti-sexual harassment politics, including the limitations of the movement including in the global South. It features both internationally recognised and emerging academics from across the fields of criminology, media and communications, film studies, gender and queer studies, and law and will appeal broadly to the academic community, activists, and beyond.
1. Introduction: Mapping The Emergence Of #Metoo, Bianca Fileborn & Rachel Loney-Howes -- Part 1. The Politics of Speaking out and Consciousness-Raising -- 2. The Politics Of The Personal: The Evolution Of Anti-Rape Activism From Second-Wave Feminism To #Metoo, Rachel Loney-Howes -- 3. Digital Feminist Activism: #Metoo And The Everyday Experiences Of Challenging Rape Culture, Kaitlynn Mendes & Jessica Ringrose -- 4. Online Feminist Activism As Performative Consciousness-Raising: A #Metoo Case Study, Jessamy Gleeson & Breanan Turner -- 5. You Say #Metoo, I Say #Mitu: China's Online Campaigns Against Sexual Abuse, Jing Zeng -- 6. A Thousand And One Stories: Myth And The #Metoo Movement, Mary Anne Franks.-Part 2. Whose Bodies Matter? #MeToo and the Politics of Inclusion -- 7. From 'Metoo' To 'Too Far'? Contesting The Boundaries Of Sexual Violence In Contemporary Activism, Bianca Fileborn & Nickie D. Phillips -- 8. This Black Body Is Not Yours For The Taking, Tess Ryan -- 9. Beyond TheBright Lights: Are Minoritized Women Outside The Spotlight Able To Say #Metoo?, Neha Kagal, Leah Cowan & Huda Jawad -- 10. 'It's Not Just Men And Women': LGBTQIA People And #Metoo, Jess Ison -- Part 3. Not All That Glitters Is Gold: #MeToo, the Entertainment Industry and Media Reporting -- 11. #Metoo And The Reasons To Be Cautious, Lauren Rosewarne -- 12. Substitution Activism: The Impact Of #Metoo In Argentina, María Cecilia Garibotti & Cecilia Marcela Hopp -- 13. Shitty Media Men, Bridget Haire, Christy E. Newman & Bianca Fileborn -- 14. Journalist Guidelines And Media Reporting In The Wake Of #Metoo, Kathryn Royal -- 15. 'It's A Reckoning That Is Long Overdue': Reconfiguring The Work Of Popular Sex Advice After #Metoo, Christy E. Newman & Bridget Haire -- Part 4. Ethical Possibilities and the Future of Anti-sexual Violence Activism -- 16. Consent Lies Destroy Lives: Pleasure As The Sweetest Taboo, Cyndi Darnell -- 17. #Metoo As Sex Panic, Heidi Matthews -- 18. Men, Masculinities, And #Metoo: Mapping Men's Responses To Anti-Rape Advocacy And Inspiring Their Support For Change, Michael Flood -- 19. Understanding Anger: Ethical Responsiveness And The Cultural Production Of Celebrity Masculinities, Rob Cover -- 20. Online Justice In The Circuit Of Capital: #Metoo, Marketization And The Deformation Of Sexual Ethics, Michael Salter -- 21. Conclusion: 'A New Day Is On The Horizon'?, Rachel Loney-Howes & Bianca Fileborn.
Keywords: Sociology; Critical criminology; Ethnology; Identity politics; Mass media and crime; Law; Sociology; Critical Criminology; Sociocultural Anthropology; Politics and Gender; Crime and the Media; Law